(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The influence of nickel as minority alloying element on the corrosion behavior of amorphous alloys (Al74Cu16Mg10)99Ni, (Al74Cu16Mg10)98Ni2 and (Al74Cu16Mg10)97Ni3 was investigated. The amorphous alloys were obtained as ribbons by Chill Block Melt Spinning (CBMS). The amorphous structure of the alloys was proven by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The corrosion rate was calculated gravimetric using continuous immersion tests for 360 hours in 3.5% NaCl solution at a temperature of 25oC. The lowest corrosion rate was found in the alloy containing 3 at. % Ni. The chemical composition of the accumulated corrosion products was studied using XRD.The influence of nickel on the local corrosion resistance of the amorphous ribbons of (Al74Cu16Mg10)100-хNiх x = 0, 1, 2, 3% alloys was investigated electrochemically in a solution of 3.5% NaCl at 25°C. Pitting potential (Epitt) and repassivation potential (Erp) were determined. It was found that most resistant to pitting corrosion was the (Al74Cu16Mg10)97Ni3 alloy, which showed the noblest pitting potential (Epitt -0.332 V) and repassivation potential (Erp -0.530 V).All obtained corrosion test results of the nickel-containing amorphous alloys were compared to the base amorphous Al74Cu16Mg10 alloy.